A Comparison of Engagement between the Attention Network Test and a Videogame-Like Version, Called the AttentionTrip. Issue 19 (26th November 2019) - Klein, Raymond M.; Vallis, Emily Howes; Chisholm, Joseph D.
ABSTRACT: The concept of attention is pivotal for our understanding of normal and abnormal human performance. The Attention Network Test (ANT) is a frequently used task for measuring three networks of attention (alerting, orienting, and executive control). Inspired by the ANT, the AttentionTrip is a videogame-like task also designed to measure these networks. The primary objective of this study, to compare the ANT and the AttentionTrip on their ability to engage the test-taker, was achieved by having the same participants' complete measures of user engagement after administration of each test. Whereas both tasks generated robust attention network scores, participants were significantly more engaged by the AttentionTrip. The AttentionTrip thus provides an alternative to the ANT that can sustain participant engagement, making it worth considering for research that involves repeated testing or when studying participants prone to boredom.